Biomechanical effects of FNS on femoral neck fractures based on different reduction quality: finite element analysis - Xu Zhang; Yazhong Zhang; Shaolong Huang; Xiangyu Qi; Wenbo Li; Yongxiang Lv; Ziqiang Zhu (BMC Musculoskeletal Disorders)
Abstract Background and objective The femoral neck system (FNS) has been extensively studied and applied for the treatment of young patients with femoral neck fractures. The purpose of this study was to explore the biomechanical impact variations in reduction qualities on femoral neck fractures, considering factors such as tip-apex distance, the positioning of the bolt in the cortical corridor of the femoral neck, and bone mineral density. Materials and methods A randomly selected volunteer was recruited, whose clinical data on the femur were collected to establish finite element models for positive reduction, anatomical reduction, and negative reduction respectively. Based on the constructed models, different scenarios were established by varying the tip-apex distance, bone mineral density, and positioning of the bolt in the cortical corridor of the femoral neck. Under a vertical load of 2100 N, the displacement and Von Mises stress (VMS) distribution of each group of models were evaluated through simulation testing. Results Under a load of 2100 N, the maximum VMS values of the femoral neck system and femoral head was recorded during negative reduction, 968.85 MPa and 80.09 MPa respectively. In addition, factors influencing the negative reduction of FNS and the femoral head were identified to be the tip-apex distance > 10 mm, the presence of osteoporosis, and the bolt positioned in the lower-middle to the third part of the cortical corridor of the femoral neck. Conclusion The displacement and stress of negative reduction were greater than those of positive reduction and anatomical reduction when the tip-apex distance > 10 mm, and the bolt was situated in the lower-middle to the third part of the cortical corridor of the femoral neck, and in the presence of osteoporosis. This means that we recommend positive repositioning over negative repositioning when anatomical repositioning is not clinically feasible.